UP TO DATE STATINS IN PRIMARY AND SECONDARY PREVENTION OF CARDIOVASCULAR DISEASES - N. F. Puchin'yan; Ya. P. Dovgalevskiy; A. V. Panina (Рациональная фармакотерапия в кардиологии)
Early and aggressive treatment of patients with risk factors and clinically manifest cardiovascular diseases is one of the priorities of modern medicine. This therapy usually consists of several components according to multifactor origin of cardiovascular disease (CVD). Correction of lipid metabolism has become one of the strategic directions. First-line agents in the treatment of dyslipidemia in patients with CVD risk factors, of course, are statins. The results of multi-center studies showing the benefits of rosuvastatin in the prevention and treatment of cardiovascular diseases are presented.